Penguatan Kompetensi Guru Dalam Pemanfaatan Teknologi Informasi dan Komunikasi (TIK) Untuk Branding dan Promosi Sekolah - Sony Zulfikasari; Malarsih Malarsih; Arief Arfriandi; Muhammad Mukhlas (I-Com: Indonesian Community Journal, 2025)
Mastery of ICT is essential for schools to enhance branding and public image in the digital era. Beyond its role in education, ICT aids in managing information, communication, and digital promotion through websites and social media. However, challenges like limited ICT skills and resources require comprehensive training, facility improvements, and strong management support. This community service initiative aimed to equip teachers with ICT skills for school branding through needs analysis, program development, implementation, evaluation, and mentoring. Results showed a significant improvement in participants' understanding, with scores rising from an average of 2.31 to 3.65 on a 4-point scale—an increase of 1.34 points. This demonstrates the effectiveness of the initiative in enhancing ICT competency for school branding, ultimately strengthening schools’ competitiveness and reputation.